Effects of dietary purified ulvan from Enteromorpha intestinalis on the growth and immune response of juvenile black tiger shrimp Penaeus monodon. - Declarador, Ritche Sale (Miag-ao, Iloilo University of the Philippines Visayas, 2014)
A 56-day growth trial was conducted to evaluate the effect of dietary purified ulvan (Elicityl, France) supplementation on growth performance, WSSV resistance and immune responses of juvenile black tiger shrimp Penaeus monodon. Four dietary treatments supplemented with 0.0 mg (Diet A), 500mg (Diets B), 1,000 mg (Diet C) and 1,500 mg (Diet D) purified ulvan kg-1 diet were formulated to contain 40.56% crude protein 7.38% crude fat, 3.5% fiber, 8.6% moisture, and 13.63% ash. Results showed that the addition of ulvan in the feeds had no adverse effect on shrimp growth and survival rate. Diets supplemented with 1,000 and 1,500 mg purified ulvan-1 kg diet resulted in a significantly better feed conversion efficiency (FCE) and protein productive value (PPV) than the control diet. In addition, enhanced immune indices were observed to shrimps fed with purified ulvan. At the level tested, 1,000 mg purified ulvan-1 kg diet showed a prolonged protective effect on WSSV challenged.
Thesis (M. S. Fisheries-Aquaculture) -- Miagao, Iloilo : U. P. Visayas, June 2014.